LITTLE KNOWN OR UNKNOWN DETAILS OF MORPHOLOGY OF MEXICAN ANOPHELES - VARGAS, LUIS (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1964)
The subgenus Anopheles is clearly differentiated from the subgenus Nyssorhynchus (spp albimanus, strodei, and argyritarsis) by subgenus Nyssorhynchus (spp albimanus, strodei, and argyritarsis) by subgenus Nyssorhynchus (spp albimanus, strodei, and argy
CIENC MEX
Keywords: KNOWN, UNKNOWN, DETAILS, MORPHOLOGY, MEXICAN, ANOPHELES; MULTIDISCIPLINARIA; ETOLOGIA; INSECTOS